IMPLEMENTASI PLTS OFF-GRID 200 WP DENGAN SISTEM MONITORING BEBAN BERBASIS ARDUINO UNO - Anggoro, Muhammad Aji; Amperawan (Teknik Elektro Polsri, 2024)
Electrical energy is energy that is very much needed for modern human life today. One of them electrical energy can be generated from solar energy or solar heat. Solar energy is a renewable energy for solar power generation systems that aim to provide renewable energy supplies to households by implementing using an off-grid PLTS system with a capacity of 200 Wp that can function effectively. The implementation of the off-grid PLTS system is carried out by several methods by means of literature, consultation, and observation. Based on the implementation of the 200 WP off-grid PLTS system with arduino uno-based load monitoring for solar panel test results show that solar panels are able to produce voltage and current in accordance with the expected specifications and it is known that energy conversion reaches high efficiency when the weather is in optimal conditions. The PZEM-004T sensor shows accurate and real-time voltage, current, and power measurements. The test results prove that the integration of the PZEM-004T sensor in the Arduino Uno-based load monitoring system for off-grid solar power plants provides significant benefits in terms of measurement accuracy and energy efficiency.